Specific Laboratory Test for Diagnosis of Multiple Sclerosis - Field, E. J.; Shenton, B. K.; Joyce, Greta (British Medical Journal, 1974)
Lymphocytes from patients with multiple sclerosis are much more susceptible to the inhibitory activity of linoleic acid (0·08 mg/ml) when tested for sensitization to thyroid by the macrophage electrophoretic mobility test (91% inhibition) than are those from normal subjects (57% inhibition). Cells from patients with a variety of other neurological diseases give 47% inhibition with linoleic acid. These differences are specific for multiple sclerosis and can be used as an in-vitro diagnostic test for the disease. Nearly 43% of clinically normal near relatives of patients with multiple sclerosis show an “anomalous” figure of about 77%; in the remainder the figure is the same as in the general population (57%). An anomalous result is compatible with lifelong freedom from M.S. Possibly a congenital anomalous handling of unsaturated fatty acids is a constant feature of the disease.